Endometrial study of abnormal uterine bleeding in perimenopausal women - E., Gomathy; V., Vandana; V., Sathyashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: AUB accounts for 70% of gynecological pathology. Prevalence of AUB is 3%-30% among reproductive aged women. Early diagnosis by endometrial biopsy is the most effective way to rule out malignancy in peri-menopausal women with AUB. TVS can be used as an aided diagnostic tool. Aims and objectives of this study is to evaluate endometrial causes of abnormal uterine bleeding in perimenopausal women and to correlate transvaginal sonography findings with histopathology by endometrial biopsy. Methods: This prospective observational study was conducted on 80 perimenopausal women with abnormal uterine bleeding. Uterine pathology, endometrial thickness, was assessed by TVS. Endometrium was considered hyperplastic if thickness is ≥10 mm in perimenopausal women and was taken up for endometrial sampling. Endometrial biopsy by Pipelle’s curette was done as an outpatient procedure and sent for HPE. Results: Total of 80 women with perimenopausal bleeding were examined during the study. Majority of the patients with AUB presented in 40-44 years age group and belonged to second parity. As per the TVS findings, 42 (52.5%) subjects had normal findings, 25 (31.3%) showed endometrial hyperplasia and remaining had other benign uterine pathology. Majority of women had ET 10 mm. The most common finding on histopathological examination was Proliferative endometrium. Conclusions: Trans vaginal scan when incorporated along with bimanual pelvic examination and Pipelle’s aspiration can enhance our anatomic diagnosis. This study proves that transvaginal findings correlate well with the histopathology findings.